2015
DOI: 10.1155/2015/831369
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic Patterns of the Upper and Lower Limbs: Baseline Data

Abstract: Objectives. To collect normative baseline data and identify any significant differences between hand and foot thermographic distribution patterns in a healthy adult population. Design. A single-centre, randomized, prospective study. Methods. Thermographic data was acquired using a FLIR camera for the data acquisition of both plantar and dorsal aspects of the feet, volar aspects of the hands, and anterior aspects of the lower limbs under controlled climate conditions. Results. There is general symmetry in skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 24 publications
(32 reference statements)
3
75
0
5
Order By: Relevance
“…In normal healthy feet, temperature patterns are symmetrical in both feet. This has recently been confirmed by Gatt et al who reported the thermographic patterns of hands and feet of healthy adults [20]. The implication is that asymmetry of temperature patterns between the feet may indicate the presence of pathology [16], which is also a logical conclusion from the findings of Gatt et al, who have demonstrated symmetry in the healthy adult.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…In normal healthy feet, temperature patterns are symmetrical in both feet. This has recently been confirmed by Gatt et al who reported the thermographic patterns of hands and feet of healthy adults [20]. The implication is that asymmetry of temperature patterns between the feet may indicate the presence of pathology [16], which is also a logical conclusion from the findings of Gatt et al, who have demonstrated symmetry in the healthy adult.…”
Section: Introductionmentioning
confidence: 61%
“…This suggests that thermography may prove useful both as a research and clinical tool in distinguishing between diabetics with and without peripheral arterial disease. Baseline thermal patterns of the hands and feet have already been reported [20]. The next logical step would be to establish thermographic data for the various categories of diabetic feet (normal, ischaemic, neuropathic, neurosichaemic) to allow comparison with normative data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] These values are significant and greater than the threshold value of 0.5 C given by the literature and could be considered as suspect in pathologies affecting corresponding body regions. [50][51][52] In this study, the temperature differences observed between the scar and the peri-scar area are above this value. Finally, this experiment shows that the temperature difference is neither related to the type nor to the age of the scar.…”
Section: Discussionmentioning
confidence: 59%
“…The lowest temperature was recorded at the distal part of the anteromedial (Z3) location of TRL. Contrary to the intact limb [23], the locations of the highest and lowest temperature sites over the TRL are close probably due to shortened length of the limb (decreased surface area) and compromised muscular and vascular tissues after amputation. Previous research with small sample sizes and diverse study designs on TRL skin temperature is con icting.…”
Section: Temperature Measurement Over the Transtibial Residual Limbmentioning
confidence: 82%